KEBERSAMAAN DALAM PERBEDAAN: STUDI KASUS MASYARAKAT CIGUGUR, KABUPATEN KUNINGAN, JAWA BARAT - Syaripulloh Syaripulloh (Sosio-Didaktika: Social Science Education Journal, 2014)
This study was conducted to gain an overview of togetherness and harmony in the life of a multi-religious society Cigugur. The study was conducted using descriptive-qualitative methods deskriktif, with the observation, in-depth interviews, and documentation study as data collection techniques. The results showed that  Cigugur people who have a diversity in religion, namely Islam, Christianity, Catholicism, Protestantism, Aga ma Djawa Sunda (ADS) can coexist peacefully. They can live together respectfully because they have strong blood ties. For the people together is more important than the divisions caused by differing views. The unifying fac tor is the chairman of each religion, in addition to the prominent role of Pangeran Djatikusumah as Madrais descent.As the dominant culture, Agama Djawa Sunda (ADS) implement a full tolerance for Cigugur society to embrace and practice religious.